Discourses of service user involvement in meeting places in Norwegian community mental health care: a discourse analysis of staff accounts. Issue 2 (7th February 2016) - Ynnesdal Haugen, Lill Susann; Envy, Andreas; Borg, Marit; Ekeland, Tor-Johan; Anderssen, Norman
Abstract: In previous research, meeting places have been favourably addressed by service users, but they have also been contested as exclusionary. In this participatory explorative study, we sought to perform a contextual analysis of meeting places in Norway based on a discourse analysis of three focus group discussions with 15 staff members. We asked the following question: how do meeting-place employees discuss their concrete and abstract encounters with service users and their experiences? We focused on service user involvement, which was largely analysed as neoliberal consultation and responsibilisation. Service users were positioned as resisting responsibility trickling down and defending staffed meeting places. Social democratic discourse was identified in the gaps of neoliberal discourse, which is noteworthy given that Norway is a social democracy. This relates to global concerns about displacements of democracy. We suggest that meeting places appear to hold the potential for staff and service users to collaborate more democratically.